Description of Leptoomus janzeni, n. gen. and n. sp. (Hymenoptera: Chalcidoidea) from Baltic amber, and discussion of its relationships and classification relative to Eupelmidae, Tanaostigmatidae and Encyrtidae - Gibson, Gary A. P. (Zootaxa, 2008)
Leptoomus janzeni, n. gen. and n. sp., is described from 5 females and 2 males in 7 pieces of Baltic amber. An enlarged acropleuron forming the entire mesopleuron places the taxon within Eupelmidae, Tanaostigmatidae or Encyrtidae (Chalcidoidea), but it has a unique combination of features that differentiates it from extant members of these families. Its structural features are compared with those that characterize the three families and it is postulated to be the sister group of Tanaostigmatidae sensu stricto + (Cynipencyrtus + Encyrtidae) based on relative structure of its pronotum, prepectus and mesothoracic spiracle, and retention of two other putative symplesiomorphies, the presence of complete furrowlike notauli and a protibial apical spicule. Conflicting character states indicate other possible relationships, including a sistergroup relationship with Cynipencyrtus + Encyrtidae based on transverse-triangular axillae and a flagellum having only seven funicular segments, or with Tanaostigmatidae s. s. based on presence of an externally visible prepectal pouch, or possibly forming a monophyletic group with Tanaostigmatidae s. s. + Cynipencyrtus based on combined acropleuralmetacoxal structure. Several features support the monophyly of Tanaostigmatidae s. s., that is excluding Cynipencyrtus and Leptoomus, but these two genera are both classified in Tanaostigmatidae sensu lato until relationships are resolved more conclusively. Features possessed by different members of Neanastatinae (Eupelmidae) suggest that this subfamily may be closely related to Tanaostigmatidae s. l. + Encyrtidae, but possible relationships of Tanaostigmatidae s. s. are also discussed if its enlarged acropleuron and other skeletomusculature features associated with jumping are convergent to similar features in the other taxa.